(untitled) (Research, Society and Development, 2020)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis or Koch’s bacillus (BK), which mainly affects the lungs, although it can occur in other organs of the body, such as bones, kidneys and meninges. TB is classified as a reemerging disease being treated as a serious public health problem. The present study aimed to quantify and analyze the sociodemographic variables of the notified cases of tuberculosis in the state of Piauí in the last ten years. This is a documentary, retrospective and descriptive study with a quantitative approach. Data were collected from the DATASUS platform. The variables studied were: sex, age group, education and area of residence. The data were compiled in graphs using the Microsoft Excel 2016® program. 10,956 TB cases were collected in the state of Piauí and, through these cases, it was found that 64.1% were male, 34.4% were middle-aged, 24.5% had low education and 72.9% resided in the urban area. The identification of the sociodemographic profile of the studied population indicated important aspects, which favor transmission and contagion, to be observed. From this, it was found that, of the cases studied, the people most affected were male, aged between 20-59 years, with low education and resident in the urban area.